2007
DOI: 10.1152/ajpregu.00331.2006
|View full text |Cite
|
Sign up to set email alerts
|

Daily restricted feeding resets the circadian clock in the suprachiasmatic nucleus of CS mice

Abstract: Abe H, Honma S, Honma K-i. Daily restricted feeding resets the circadian clock in the suprachiasmatic nucleus of CS mice. Am J Physiol Regul Integr Comp Physiol 292: R607-R615, 2007. First published September 21, 2006; doi:10.1152/ajpregu.00331.2006.-Circadian rhythms in clock gene expressions in the suprachiasmatic nucleus (SCN) of CS mice and C57BL/6J mice were measured under a daily restricted feeding (RF) schedule in continuous darkness (DD), and entrainment of the SCN circadian pacemaker to RF was examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 37 publications
1
40
0
Order By: Relevance
“…When rodents are subjected to a restricted feeding schedule, the patterns of diurnal variation of various physiological functions change; e.g., locomotory activity and plasma corticosterone levels increase before feeding time [21]. Recent studies have suggested that rhythms of clock gene expression in the SCN show a fixed phase-relationship with feeding time [22,23], indicating that the circadian pacemaker in the SCN can be entrained by the restricted feeding schedule. Thus these observations may support our conclusion that the SCN could form and retain a time memory and work as a timer for changing T cor in rats.…”
Section: Discussionmentioning
confidence: 99%
“…When rodents are subjected to a restricted feeding schedule, the patterns of diurnal variation of various physiological functions change; e.g., locomotory activity and plasma corticosterone levels increase before feeding time [21]. Recent studies have suggested that rhythms of clock gene expression in the SCN show a fixed phase-relationship with feeding time [22,23], indicating that the circadian pacemaker in the SCN can be entrained by the restricted feeding schedule. Thus these observations may support our conclusion that the SCN could form and retain a time memory and work as a timer for changing T cor in rats.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated entrainment of animal behavior by daily cycles of food availability in rats [11], mice [12], kowaris [13], sparrows [14], Kuzu rats [15], rabbits [16], squirrel monkeys [17], and other species. Because two separate behavioral components were observed when animals were exposed simultaneously to environmental cycles of light-darkness and food restriction, and because the so-called ''food anticipatory'' component persisted in constant darkness after the main circadian pacemaker in the hypothalamic suprachiasmatic nucleus had been ablated [18], some authors assumed the existence of distinct input pathways to a ''light-entrainable pacemaker'' and a ''food-entrainable pacemaker'' [19].…”
Section: Introductionmentioning
confidence: 99%
“…The effects of daytime RF are well documented in the literature in a number of species, including nocturnal rodents, such as Mus musculus and Rattus norvegicus (Abe et al, 1989(Abe et al, , 2007Boulos et al, 1980;Castillo et al, 2004;Challet et al, 1997;Marchant & Mistlberger, 1997;Rosenwasser et al, 1981). Animals adapt to conditions of limited food availability by increasing food-seeking behavior, or FAA, in the hours preceding food presentation.…”
Section: Discussionmentioning
confidence: 99%